PENGARUH DIVIDEND POLICIES TERHADAP STOCK PRICE VOLATILITY (STUDI EMPIRIS PADA PERUSAHAAN INDEKS HIGH DIVIDEND 20 YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2020-2024) - Suci Indah Sari; Rini Frima; Lisa Amelia Herman (Universitas Sarjanawiyata Tamansiswa, 2025)
This study aims to analyze the effect of dividend policies on stock price volatility, with asset growth, leverage, and size as control variables. The population in this study consists of all companies listed in the High Dividend 20 Index for the period 2020 to 2024. The sampling technique used in this study is purposive sampling. The results show that the dividend payout ratio and dividend yield have no effect on stock price volatility, while the control variables asset growth, leverage, and size have a negative and significant effect on stock price volatility. Simultaneously, the dividend payout ratio, dividend yield, asset growth, leverage, and size influence stock price volatility